Ectopic beats and editing methods for Poincaré-plot-based HRV. (1st January 2011) - Singh, Butta; Singh, Dilbag
In this study, the effect of ectopic beats and its editing methods on the Poincaré plot based HRV indices SD1 and SD2 have been assessed. Ectopic free RR interval time series of length 900, 500 and 300 for 10 healthy subjects were analysed by inserting low, medium and high level artificial ectopic beats. SD1 was found to be more sensitive to ectopic beats than SD2. The effect has been found to be the function of amount and level of ectopic beats and RR interval data length. The editing methods are found to be more efficient for long-term data.